2017
DOI: 10.1007/s13209-017-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vocational education on adult skills, employment and wages: What can we learn from PIAAC?

Abstract: We have shown that vocational education does not perform as well as academic education both in labour market outcomes and in the level of basic skills, including literacy and numeracy. This is especially true for higher education. Only at the upper secondary or post-secondary level does vocational education perform slightly better than academic education in the probability of being currently employed as well as in the time spent in paid employment, although the differences we find are small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 22 publications
5
49
0
2
Order By: Relevance
“…The positive effect of age was even higher among Finnish vocational upper secondary schoolers, who improved their skills during the upper secondary level studies to the extent that they closed the skills gap that existed between general and vocational upper secondary school students by the beginning of their upper secondary level studies.Instead, the development of digital skills among general upper secondary education students was found to be more diminutive. This observation is interesting, as the previous assumption was that vocational education is not as effective as academic education, in this case general upper secondary education, in terms of outcomes for including such skills (seeBrunello & Rocco 2017). These findings also lead one to turn more attention to the curricula.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The positive effect of age was even higher among Finnish vocational upper secondary schoolers, who improved their skills during the upper secondary level studies to the extent that they closed the skills gap that existed between general and vocational upper secondary school students by the beginning of their upper secondary level studies.Instead, the development of digital skills among general upper secondary education students was found to be more diminutive. This observation is interesting, as the previous assumption was that vocational education is not as effective as academic education, in this case general upper secondary education, in terms of outcomes for including such skills (seeBrunello & Rocco 2017). These findings also lead one to turn more attention to the curricula.…”
mentioning
confidence: 68%
“…This effect was particularly strong for the skills needed in problem-solving in technology-rich environments(OECD 2012;. Correspondingly,Brunello and Rocco (2017) argued based on the PIAAC data from 17 countries, that the level of proficiency in basic skills revealed that vocational education is less effective than academic education at the same level of education.…”
mentioning
confidence: 99%
“…It can be seen that awareness of adult numeracy skills and the factors likely to influence these levels is increased steadily all over the world. Nevertheless, a limited number of studies have been found in the literature (Anders, et al, 2012;Brunello, 2017;Gustafsson, 2016;Heisig & Solga, 2015;Meroni, Vera-Toscano, & Costa, 2015) specifically focused on PIAAC numeracy skills. However, unlike OECD arguments based on educational policy approaches, St.…”
Section: Piaacmentioning
confidence: 99%
“…Dans l'ensemble, au niveau du deuxième cycle de l'enseignement secondaire, ceux qui suivent une filière professionnelle auront globalement davantage de chances de trouver un emploi, consacreront une part plus importante de leur temps de travail potentiel à une activité rémunérée mais percevront un salaire horaire légèrement inférieur par rapport aux élèves de filières générales (Brunello et Rocco, 2014). Ainsi, en moyenne dans les pays de l'OCDE dont les données sont disponibles, 79 % des 25-34 ans diplômés de la filière professionnelle du dossier deuxième cycle du secondaire occupent un emploi -soit un taux supérieur de 10 points de pourcentage à celui qui s'observe parmi les 25-34 ans diplômés de la filière générale du deuxième cycle du secondaire.…”
Section: Constats Sur L'employabilité Des Jeunes Diplômésunclassified